Optical and gas-sensing properties, and electronic structure of the mixed-phase CaCu3Ti4O12/CaTiO3 composites - Oliveira, L. H.; Ramírez, M. A.; Ponce, M. A.; Ramajo, L. A.; Albuquerque, A. R.; Sambrano, J. R. [UNESP]; Longo, E.; Castro, M. S.; La Porta, F. A. (Elsevier, 2017)
Combined experimental and theoretical investigations were conducted on the electronic structure, as well as the optical and gas-sensing properties of mixed-phase CaCu3Ti4O12/CaTiO3 (CCTO/CTO) composites, which were synthesized by a solid-state reaction using various milling durations. Our results revealed that these CCTO/CTO composites have a broad photoluminescence (PL) emission band located at 450 nm, which is strongly influenced by the milling process duration. Scanning electron microscopy images confirmed that the use of longer milling durations favored the formation of pores and increased the active surface area of the CCTO/CTO thick films. The thick films were prepared using the screen-printing technique, and hence, could be structured for gas-sensing applications. Our theoretical findings may further elucidate the electronic structure associated with the interfacial band alignment (type I-straddling gap) of the CCTO/CTO composite systems.
Keywords: CCTO/CTO composites; DFT; Gas sensing; Photoluminescence; Screen-printing technique